2021
DOI: 10.3390/ijerph182111644
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Unified Protocol for a Japanese Patient with Post-Traumatic Stress Disorder and Multiple Comorbidities: A Single-Case Study

Abstract: (1) Background: The efficacy of the Unified Protocol (UP), a transdiagnostic cognitive-behavioral therapy, with trauma-focused exposure has not been sufficiently demonstrated for post-traumatic stress disorder (PTSD) with multiple comorbidities. This study examined the effects of UP treatment with trauma-focused exposure on symptoms of PTSD and comorbidities in a client who was hesitant about exposure. (2) Methods: The client, who had comorbid dysthymia, social anxiety disorder, agoraphobia, and bulimia nervos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
0
0
Order By: Relevance
“…To intervene in this pattern, the UP teaches emotion regulation skills to increase willingness to experience strong emotions without relying on self-defeating escape or avoidance strategies. Accumulating evidence supports the success of the UP in reducing symptoms of heterogeneous emotional disorders (Cassiello-Robbins et al, 2020); self-harm (Bentley, 2017); anger (Cassiello-Robbins, et al, 2020); irritability (Grossman, & Ehrenreich-May, 2020); and, particularly germane to the present study, PTSD (Gutner et al., 2022; Hood et al, 2021; Kato, et al, 2021 ; O’donnell et al, 2021; Varkovitzky et al, 2018).…”
Section: Introductionsupporting
confidence: 67%
“…To intervene in this pattern, the UP teaches emotion regulation skills to increase willingness to experience strong emotions without relying on self-defeating escape or avoidance strategies. Accumulating evidence supports the success of the UP in reducing symptoms of heterogeneous emotional disorders (Cassiello-Robbins et al, 2020); self-harm (Bentley, 2017); anger (Cassiello-Robbins, et al, 2020); irritability (Grossman, & Ehrenreich-May, 2020); and, particularly germane to the present study, PTSD (Gutner et al., 2022; Hood et al, 2021; Kato, et al, 2021 ; O’donnell et al, 2021; Varkovitzky et al, 2018).…”
Section: Introductionsupporting
confidence: 67%
“…En la Tabla II, se presentan los principales resultados en esas categorías, se incluyen sólo ar-tículos publicados en 2021 y 2022 y que contengan todos los términos de la búsqueda ¨psicoterapia basada en evidencia AND tratamientos combinados AND severidad comorbili-dad¨. Se observa que tanto en grandes poblaciones (Zeibig et al, 2021), como en estudios de caso único (Kato et al, 2021), se impone la necesidad de superar el esquema de clasificación de diagnóstico específico, por uno que aborde la complejidad y comorbilidad de los síntomas psi- (Rush et al, 2022).…”
Section: Resultsunclassified
“…This is important since it has been previously reported that, despite the advantages of the group format, the UP is more accepted in the individual format . However, because the sample was not very large, the data presented must be taken with caution since they do not present strong statistical analyses or more measurement instruments that allow showing a better significance, as was shown in schizoid personality and post-traumatic stress disorder (Kato et al, 2021). Another important element is that no evaluation was applied that would allow us to the temperament of the patients (neuroticism/extraversion), and the changes that could have been generated due to the UP, which has already been reported today (Zemestani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%